IMPROVEMENT OF GRAPH INTERPRETATION ABILITY USING HYPERTEXT-ASSISTED KINEMATIC LEARNING AND FORMAL THINKING ABILITY - Manurung, S. R.; Mihardi, S.; Rustaman, N. Y.; Siregar, N. (Jurnal Pendidikan Fisika Indonesia, 2018)
The effectiveness of hypertext media in improving graph interpretation ability is investigated in this paper. In addition, joint ability of the formal thinking to improve the graph ability of prospective students is considered. The research design used is the one-group pretest-posttest experimental design is carried out in the research by taking 36 students on from Physics Education Program in one institute for teacher education in Medan. The test consists of graph interpretation ability test in the topic of kinematics and Test of Logical Thinking (TOLT or formal thinking) before learning and graph interpretation ability test after learning. The data are then analysed by using SPSS based two ways Analisys of Variance (ANOVA) method. The results show that the ability to interpretate graph is significantly improved by using hypertext media assisted kinematic learning.